Perspektif Ekonomi Makro Islam Terhadap Pemanfaatan Sumber Daya Alam - Naili Nuril Aufa Manik; Agung Wibowo; Khairina Tambunan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2021)
This study aims to analyze the Islamic Macroeconomic Perspective on the Utilization of Natural Resources, as well as the factors that influence it. In this study, the researcher used descriptive-analytical techniques and a qualitative approach. Sources of data obtained from literature studies relevant to the topic raised. Data analysis in this study used a deductive and deductive approach. Production in Islamic macroeconomics means an effort to add value in order to preserve the survival of living things and be used to meet the needs of all living creatures created by God. In the context of this research, Islam distributes several operational principles that are useful for the operational use of natural resources so that natural resources are used properly and wisely.